HDAC6 Inhibition Corrects Electrophysiological and Axonal Transport Deficits in a Human Stem Cell‐Based Model of Charcot‐Marie‐Tooth Disease (Type 2D). Issue 2 (26th December 2021) - Smith, Alec S.T.; Kim, Jong Hyun; Chun, Changho; Gharai, Ava; Moon, Hyo Won; Kim, Eun Young; Nam, Soo Hyun; Ha, Nina; Song, Ju Young; Chung, Ki Wha; Doo, Hyun Myung; Hesson, Jennifer; et al.
Abstract: Charcot‐Marie‐Tooth disease type 2D (CMT2D), is a hereditary peripheral neuropathy caused by mutations in the gene encoding glycyl‐tRNA synthetase ( GARS1 ). Here, human induced pluripotent stem cell (hiPSC)‐based models of CMT2D bearing mutations in GARS1 and their use for the identification of predictive biomarkers amenable to therapeutic efficacy screening is described. Cultures containing spinal cord motor neurons generated from this line exhibit network activity marked by significant deficiencies in spontaneous action potential firing and burst fire behavior. This result matches clinical data collected from a patient bearing a GARS1 P724H mutation and is coupled with significant decreases in acetylated α‐tubulin levels and mitochondrial movement within axons. Treatment with histone deacetylase 6 inhibitors, tubastatin A and CKD504, improves mitochondrial movement and α‐tubulin acetylation in these cells. Furthermore, CKD504 treatment enhances population‐level electrophysiological activity, highlighting its potential as an effective treatment for CMT2D. Abstract : Human induced pluripotent stem cell (hiPSC)‐derived spinal neurons bearing mutations in GARS1 exhibit mitochondrial transport and electrophysiological deficits. Aberrant GARS1‐HDAC6 protein interactions are present in GARS1 P234KY, but not GARS1 P724H, neurons. In both mutant genotypes, HDAC6 inhibition improves mitochondrial transport and electrophysiological function. Results suggest that HDAC6 inhibition could be therapeutic for Charcot‐Marie‐Tooth disease (type 2D), and the observed improvements in neuronal function occur via non‐disease related mechanisms.